A supplier review system as part of the government procurement system for China - Zhang, Xinglin (2008)
A supplier review system can play a significant role in ensuring the enforcement of procurement rules through its deterrent and redress effects. This thesis aims at providing a critical analysis of the current Chinese supplier review system and identifying and evaluating options for improvement of the Chinese system, based on the analysis of provisions on supplier review contained in the UNCITRAL Model Law on Procurement, the GPA, the EU Remedies Directives and APEC Non-Binding Principles on Government Procurement.